Entropy optimized radiative nanomaterial flow beyond classical concepts of heat and mass fluxes - T. Hayat; Muhammad Fahim; Aneeta Razaq; Mohamed Abdalla (Case Studies in Thermal Engineering)
Involvement of nanomaterials in such manufacturing processes is not underestimated. Especially the rheological nanomaterials for heat transfer are useful in processes related to cooling microchips, solar energy and thermal energy technology. Experimental studies have now witnessed the efficiency for utilization of nanoparticles regarding heat transportation enhancement. With such consideration here we analyze magnetohydrodynamic (MHD) flow of tangent hyperbolic nanomaterial. Analysis involves novel concepts of nonlinear mixed convection and entropy generation. New concepts of heat and mass fluxes for thermal and solutal transport rates are utilized. Brownian movement and thermophoresis behaviors are under consideration. Heat expression contains thermal radiation. Entropy optimization with Cattaneo-Christov theory through entire new concept of radiation is discussed. Nonlinear ordinary differential system by adequate transformations is derived. Optimal homotopy analysis technique (OHAM) for convergent solutions is implemented. Analysis of flow, temperature, rate of entropy and concentration is provided. Performances of Nusselt and Sherwood numbers for influential variables are graphically explored. Here one can conclude that flow through buoyancy ratio and magnetic field respond in a reverse manner. Temperature and entropy rate for radiation have same trend. Higher thermal Biot number lead to enhancement of Nusselt number and thermal field. Higher approximation of solutal relaxation time variable corresponds to rise of concentration. An intensification in rate of entropy through diffusion variable is witnessed.